The microwave measurements of (N₂)хАr₁₋x solid solutions - Kempinski, W.; Stankowski, J. (Физика низких температур, 1995)
A full range of solid solutions (N₂)хАr₁₋x (0 < x <1) have been examined with an x-band microwave dielectrometer. The real part of the permittivity e' versus temperature T for this non-polar system has been measured with a high accuracy (10⁻⁶) at temperatures between 1.5-75 K. A comparative (x, T) phase diagram is constructed with a β-α structural phase transition and the problem of transition to the orientational glass is discussed.